Brain Hypoxia Is Associated With Short-term Outcome After Severe Traumatic Brain Injury Independently of Intracranial Hypertension and Low Cerebral Perfusion Pressure - Oddo, Mauro; Levine, Joshua M.; Mackenzie, Larami; Frangos, Suzanne; Feihl, François; Kasner, Scott E.; Katsnelson, Michael; Pukenas, Bryan; Macmurtrie, Eileen; Maloney-Wilensky, Eileen; Kofke, W. Andrew; LeRoux, Peter D. (Neurosurgery, 2011)
Abstract BACKGROUND Brain hypoxia (BH) can aggravate outcome after severe traumatic brain injury (TBI). Whether BH or reduced brain oxygen (Pbto2) is an independent outcome predictor or a marker of disease severity is not fully elucidated. OBJECTIVE To analyze the relationship between Pbto2, intracranial pressure (ICP), and cerebral perfusion pressure (CPP) and to examine whether BH correlates with worse outcome independently of ICP and CPP. METHODS We studied 103 patients monitored with ICP and Pbto2 for > 24 hours. Durations of BH (Pbto2 < 15 mm Hg), ICP > 20 mm Hg, and CPP < 60 mm Hg were calculated with linear interpolation, and their associations with outcome within 30 days were analyzed. RESULTS Duration of BH was longer in patients with unfavorable (Glasgow Outcome Scale score, 1–3) than in those with favorable (Glasgow Outcome Scale, 4–5) outcome (8.3 ± 15.9 vs 1.7 ± 3.7 hours; P < .01). In patients with intracranial hypertension, those with BH had fewer favorable outcomes (46%) than those without (81%; P < .01); similarly, patients with low CPP and BH were less likely to have favorable outcome than those with low CPP but normal Pbto2 (39% vs 83%; P < .01). After ICP, CPP, age, Glasgow Coma Scale score, Marshall computed tomography grade, and Acute Physiology and Chronic Health Evaluation II score were controlled for, BH was independently associated with poor prognosis (adjusted odds ratio for favorable outcome, 0.89 per hour of BH; 95% confidence interval, 0.79-0.99; P = .04). CONCLUSION Brain hypoxia is associated with poor short-term outcome after severe traumatic brain injury independently of elevated ICP, low CPP, and injury severity. Pbto2 may be an important therapeutic target after severe traumatic brain injury.